Differential Analysis on Mental Health Level of Physical Education Majors - Qianqian Yang; Qiuxiang Shi; Luobin Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
College students can promote both physical fitness and mental health by taking a suitable amount of physical exercise at the right time. However, few scholars have conducted differential analysis on the mental health level of college students under the intervention of physical exercise, not to mention that of physical education (PE) majors. To fill up the gap, this paper carries out a differential analysis on the mental health level of PE majors. Firstly, the mental health level of PE majors was evaluated in 11 aspects, and a graded response model was established based on the 11 indices. Next, the mental health level of PE majors was subjected to fuzzy comprehensive evaluation (FCE). Finally, the mental health differences between PE majors and college students in other majors were analyzed accurately. The results show that the mental health level of physical education majors varies with genders, ages, grades, school types, durations per physical exercise, weekly frequencies of physical exercise, sports venues, and skill levels. The research findings provide a reference for further research of PE majors and their mental health level.